Intermolecular interactions between supramolecular structures and molecules of interest in the food - Rezende, Jaqueline de Paula (Universidade Federal de Viçosa, 2019)
Faced with the constitutional diversity and dynamism of these structures. It S possible to develop new structures with functional characteristics and properties of interest to the food area. The present work was divided into 3 scientific articles and aimed to develop three supramolecular structures, one with sensing capacity and two as nanocarriers of hydrophobic molecules. In the first article, polydiacetylene (PDA) was used in the development of sensors to detect the presence of the antibiotic enrofloxacin (ENRO) in aqueous medium at 30 º C. Sensor nanostructures, so-called nanoblends (NB), were produced from the mixture of PDA, triblock copolymers (TC) and sodium dodecy] sulfate surfactant (SDS). The PDA/ TC/ SDS NBs were able to detect ENRO at a concentration five times lower than the maximum limit allowed by the European Union. The increased sensitivity of the nanosensor containing SDS was attributed to the energy released from the intermolecular interaction between ENRO and SDS, favoring the blue- red colorimetric transition process of the PDA. The response surface methodology showed that both ENRO concentration and SDS influence the colorimetric response (CR) of the sensor, with the maximum CR obtained in [ENRO] = 2 uM and [SDS] = 14.6 mM. The colorimetric transition rate was also evaluated, and NB containing 11.6 mM SDS required only 22 min to reach 40% RC, which is easily visible. The second article presented the thermodynamics and kinetics of formation of bovine lactoferrin (bLF) - epigallocatechin-3-gallate (EGCG) complex obtained by surface plasmon resonance technique (SPR). Fluorescence spectroscopy (FS) was also used to obtain thermodynamic data. Formation of the thermodynamically stable bLF-EGCG complex (AG°spr ≈ -29.00 kJ mol-¹, AG°fs ≈ -26.00 kJ mol-¹) at pH = 7.0 was entropically driven (AH°spr = 14.26, AH°fs = 10.20 kJ mol-¹ and TΔS°spr ≈ 43.00, TΔS°fs ≈ 36.00 kJ mol-¹). As the thermodynamic data of the two techniques were similar, itis suggested that the interaction between the biomolecules occurred in regions close to the tryptophan present in the protein. The increase in temperature favored the stability of the bLF-EGCG complexcausing an increase in the association (ka) and dissociation (ka) constants of the complex. In the third article, the effect of the chemical structure of polyphenol resveratrol (RES) on interaction with human serum albumin (HSA) was evaluated. Thus, the Kinetic and thermodynamic parameters of complex formation between HSA and RES and one of its analogs (RESAn1) were evaluated by SPR. The binding constant (Kb) and kinetic constants of association (ka) and dissociation (kd) showed that the HSA-ResAn1 interaction (Kb(hsa-Resan1)~ 3.94 x 10³ L mol-¹, ka(hsa-Resan1)~1.70 x 10³ M-¹ s-¹, kd(hsa-Resan1)~ 0.43 S-¹) was more intense than HSA-Res (Kb(hsa-Res) ~2.60 x 10³ L mol-¹, ka(sa-Res) ~ 1.20 x 10³M-¹s-¹, kd (hsa-Res)~ 0.46 s-¹). The less polar structure of ResAn1 relative to Res contributes to its access to the hydrophobic regions within the HSA. The formation of both complexes was entropically driven (TΔS° hsa-res ~33.8 and TΔS° hsa-resan1~ 56.4 KJ mol-¹) and favored with increasing temperature. This study showed that small changes in the structure of a bioactive may influence its interaction with the HSA. Regardless of the purpose of the supramolecular structures, the works sought to evaluate and understand the interactions between the molecules that make up the system, as well as between the system and molecules present in their environment. Therefore, the objective of these works was to provide data that contribute to the optimization of the use and application of the developed structures. Keywords: Optical nanosensor. Antibiotic detection. Thermodynamic binding. Kinetic constants. Complex activated.

Estruturas supramoleculares são sistemas dinâmicos em razão da capacidade de modificar sua constituição em resposta a variações do meio circundante (solvente) e/ou de fatores físicos (temperatura, pressão, campo elétrico) e/ou interação com outras moléculas. Diante da diversidade constitucional e dinamismo dessas estruturas, é possível desenvolver novas estruturas com características e propriedades funcionais de interesse para a área de alimentos. O presente trabalho foi dividido em 3 artigos científicos e teve como objetivo desenvolver três estruturas supramoleculares, uma com capacidade sensora de detecção e duas como nanocarreadoras de moléculas hidrofóbicas. No primeiro artigo, o polidiacetileno (PDA) foi utilizado no desenvolvimento de sensores para detectar a presença do antibiótico enrofloxacina (ENRO) em meio aquoso, à 30 ºC. As nanoestruturas sensoras, conhecidas como nanoblendas (NB), foram produzidas a partir da mistura de PDA, copolímeros tribloco (CT) e surfactante dodecil sulfato de sódio (SDS). As NBs de PDA/CT/SDS foram capazes de detectar ENRO em uma concentração cinco vezes menor do que o limite máximo permitido pela União Europeia. O aumento da sensibilidade do nanossensor que continha SDS foi atribuído à energia liberada a partir da interação intermolecular entre ENRO e SDS, favorecendo o processo de transição colorimétrica azul-vermelho do PDA. A metodologia de superfície de resposta mostrou que tanto a concentração de ENRO quanto de SDS influenciaram na resposta colorimétrica (RC) do sensor, sendo que a RC máxima obtida foi em [ENRO] = 2 uM e [SDS] = 14,6 mM. A taxa de transição colorimétrica também foi avaliada, sendo que a NB contendo 11,6 mM de SDS gastaria apenas 22 min para atingir 40% de RC, que é facilmente visível. O segundo artigo apresentou a termodinâmica e cinética de formação do complexo lactoferrina bovina (bLF) - epigalocatequina-3-galato (EGCG) obtidas pela técnica de ressonância plasmônica de superfície (SPR). A espectroscopia de fluorescência (FS) também foi empregada para obtenção dos dados termodinâmicos. A formação do complexo bLF-EGCG termodinamicamente estável (AG°spr ≈ -29,00 kJ mol-¹, AG°fs ≈ - 26,00 kJ mol-¹) em pH = 7,0 foi impulsionada entropicamente (ΔH°spr = 14,26, ΔH°fs = 10,20 kJ mol-¹ and TΔS°spr ≈ 43,00, TΔS°fs ≈ 36,00 kJ mol-¹). Como os dados termodinâmicos das duas técnicas foram similares, sugere-se que a interação entre as biomoléculas ocorreram em regiões próximas aos triptofanos presentes na proteína. O aumento da temperatura favoreceu a estabilidade do complexo bLF-EGCG causando aumento nas constantes de associação (ka) e de dissociação (kd) do complexo. No terceiro artigo foi avaliado o efeito da estrutura química do polifenol resveratrol (RES) na interação com a albumina do soro humano (HSA). Assim, os parâmetros cinéticos e termodinâmicos de formação de complexo entre a HSA e RES e um de seus análogos (RESAn1) foram avaliados por SPR. A constante de interação (Kb) e constantes cinéticas de associação (ka) e dissociação (kd) mostraram que a interação HSA-RESAn1 (Kb(HSA-RESAn1)~3,94; X 10³L mol-¹, ka(hsa-rEsan1)~ 1,70 x 10º M-¹s-¹, kd(hsa-rEsAnt)~ 0,43 S-¹) foi mais intensa que HSA-RES (Kb (hsa-rEs)~2,60 X 10³ L mol-¹, ka(hsa-res)~ 1,20 x 10ºM-¹s-¹, kd(hsa-res) ~0,46 s-¹). A estrutura menos polar do RESAnl em relação a do RES contribui para seu acesso às regiões hidrofóbicas no interior da HSA. A formação de ambos complexos foi entropicamente dirigida (TΔSº hsa-res ~ 33,8 and TΔS° hsa-REsAn1~ 56,4 KJ mol-¹) e favorecida com o aumento da temperatura. Esse estudo mostrou que pequenas mudanças na estrutura de um bioativo pode influenciar na sua interação com a HSA. Independente da finalidade das estruturas supramoleculares, os trabalhos buscaram avaliar e compreender as interações entre as moléculas que compõe o sistema, bem como, entre o sistema e moléculas presentes no meio em que se encontram. Portanto, o objetivo desses trabalhos foi fornecer dados que contribuam para a otimização do uso e aplicação das estruturas desenvolvidas. Palavras-chave: Nanossensor ótico. Detecção de antibiótico. Termodinâmica de interação. Constantes cinéticas. Complexo ativado.
Interações intermoleculares entre estruturas supramoleculares e moléculas de interesse na área de alimentos
Keywords: Forças intermoleculares; Nanoestruturas; Detectores; Proteínas transportadoras; Química, Física, Físico-Química e Bioquímica dos Alim. e das Mat.-Primas Alimentares